Washington Online Virtual Campus: Infusing culture in dispersed Web-based higher education - Hai-Jew, Shalin (My University, 2010)
Started in 1997, WashingtonOnline Virtual Campus (WAOL) consists of a consortium of 34 community colleges around Washington State to provide asynchronous online learning. WAOL bears many of the features of a loosely coupled organization with its geographically dispersed frontline instructors, fragmented external environment, modularity of courses and supervision, and its use of enhanced leadership and technology to communicate a culture. Recent surveys of its administration, instructors, and staff found disparities in various constituencies’ perspectives on the organization’s culture, decision-making, values, brand or reputation, communications, and WAOL’s authorizing environment. Research suggests that WAOL benefits from some aspects of loose coupling: greater adaptive abilities and responsiveness to the State’s college system; “fast” course development and launching; and isolated breakdowns. There is, however, a persistent difficulty in conveying a cohesive culture. There is a perception of WAOL’s invisibility among its varied constituencies. This organization is at a crossroads, with the threat of colleges disconnecting from this consortium. WAOL should redefine its direction and purpose, such as coupling with local universities to provide not only associates degrees but full Baccalaureate and/ or Masters degrees. It may strengthen its position by improving learner supports, publicizing its decisions, creating a stronger sense of virtual community among the instructors (as in its recent creation of an online community for instructors), increased participative decision-making and use of line faculty and staff insights, and greater course varieties.
Keywords: Leadership; Culture; Organizational culture; Partnership; Disintermediation; Virtual organization; Loosely coupled organization; Distance learning; Virtual culture; Technology mediation